Sense of online betrayal, brand hate, and outrage customers’ anti-brand activism - Hai Ninh Nguyen; Thanh Binh Nguyen (Innovative Marketing, 2021)
The current study develops a research model and explores the correlation between customer sense of online betrayal, brand hate, and anti-brand activism. The outrage customers’ anti-brand behaviors consist of negative online word of mouth, online public complaining, and online boycott. Data from an online survey of 383 online shoppers were used to test seven proposed hypotheses. The partial least square–structural equation modeling (PLS-SEM) was adopted to assess the measurement and structural model. The findings showed that the sense of online betrayal positively and significantly affects brand hate and anti-brand behaviors. In addition, brand hate is also the leading cause of customers’ anti-brand actions. The present study highlights the mediation role of brand hate in eliciting revenge from consumers subjected to online betrayal. This study also gives some recommendations to customers to stop the misconduct behaviors of online betrayals, such as spreading their betrayal cases to friends and relatives via social media, then asking for supports and help from governmental and legal agencies and participating in boycotts; raising boycott movements against the betraying brand should be considered as the most extreme punishment.